Evaluación agronómica de plántulas de Guarango (Caesalpinia spinosa) propagadas por semillas, con tres tipos de sustratos y cuatro tipos de tratamientos pregerminativos en Laguacoto I. - García Ramos, Paúl Adrián (2018)
The Guarango is multipurpose, because it provides more than one function or service in a system of land use. It is also a forage plant, honey and its wood is hard, suitable for many uses and applications. The application of pregerminative treatments is important to break the latency of the seeds. The objectives of this research were: i.-) Determine which substrate helped the best germination of Guarango seeds. ii.-) Identify the best pregerminative treatment for germination of Guarango seeds. iii.-) Carry out the economic analysis cost benefit ratio (B/C). The present investigation was carried out in the province of Bolívar, canton Guaranda, Veintimilla parish, sector Laguacoto I. Guarango seeds were used with three types of substrates and four pre-germination treatments. A design: Complete Random Blocks (DBCA) in factorial arrangement of 3 x 4 x 3 repetitions, and an Analysis of variance ADEVA. Tukey test was performed at 5% to compare averages of Factor A, Factor B and interaction A x B. Analysis of correlation and simple linear regression and economic analysis benefit / cost ratio (B/C). The best substrate was peat with a survival percentage of 95.4%, as for the pregerminative treatment was sanding with 94.2%. The best treatment was T11, which presented a net benefit of $ 9.24 USD; a benefit/cost ratio: B/C of $ 1.48 USD and an income/cost ratio I/C of $ 0.48 USD. This means that the producer of Guarango plant for every dollar invested, has a profit of $ 0.48 USD.